A qualitative study to explore the attitudes of women and obstetricians towards caesarean delivery in rural Bangladesh - Begum, Tahmina; Sarker, Malabika (BMC pregnancy and childbirth, 2018)
Caesarean section is a lifesaving surgical intervention for women and their newborns, though overutilization is a public health concern. The caesarean rate in Bangladesh is approximately 23% overall, and in private facilities it is over 70%. It is essential to know both the supply side (obstetricians) and demand side (parturient women) views on caesarean birth in order to formulate specific interventions to address the escalating rate of caesareans.